A two‐surface damage‐plasticity model based on a Drucker—Prager yield criterion. Issue 1 (24th March 2023) - Zhang, Jian; Brepols, Tim; Reese, Stefanie
Abstract: A gradient‐extended two‐surface damage‐plasticity model based on a von Mises yield criterion has been proposed by [1, 2], which can be flexibly adapted to (quasi‐)brittle‐like, ductile‐like, or various material behaviors in between. However, the von Mises yield criterion does not take into account the effect of hydrostatic pressure, therefore it can hardly model the failure behavior of pressure‐sensitive materials such as geomaterials and some metals. For this reason, a pressure‐dependent two‐surface damage‐plasticity model based on the Drucker‐Prager yield criterion is proposed in the current work, and the nonlinear hardening is also included. Plasticity and damage are treated as distinct but coupled dissipative phenomena by a two‐surface approach. Furthermore, the numerical implementation of the Drucker‐Prager yield criterion is discussed in this study, and the return mapping procedures of the smooth portion and the vertex of the cone are discussed in detail.